A Process Evaluation of a Kentucky Court Improvement Initiative. (6th July 2016) - Thomas, Tammi A.; Collins‐Camargo, Crystal; Corey Boes, R.
Abstract : This article describes a court improvement initiative designed to promote uniformity and improved court practice with the ultimate goal of the improvement of outcomes for children and families. The article focuses on the results of interviews and focus groups conducted as part of the evaluation of this initiative. Twelve jurisdictions were purposively selected to exhibit a range of family court and non–family court jurisdictions in rural and middle‐sized locations. The discussion of the qualitative results focuses on changes in court practice and the impact of the initiative on case time. Key Points for the Family Court Community: This initiative was undertaken to promote consistency of practice in family law matters. We explain how the rules impact the following areas: divorce; property distribution as a result of divorce; custody, visitation, and child support; adoption; termination of parental rights; domestic violence, child abuse, and neglect; and status offenses. We describe the impact of a state‐wide court improvement initiative. We identify areas of improvement within court operations that may be modified in other jurisdictions.